Environmental exposures and systemic hypertension are risk factors for decline in lung function. Issue 12 (30th July 2018) - Miele, Catherine H; Grigsby, Matthew R; Siddharthan, Trishul; Gilman, Robert H; Miranda, J Jaime; Bernabe-Ortiz, Antonio; Wise, Robert A; Checkley, William
Abstract : Background: Chronic lung disease is a leading contributor to the global disease burden; however, beyond tobacco smoke, we do not fully understand what risk factors contribute to lung function decline in low-income and middle-income countries. Methods: We collected sociodemographic and clinical data in a randomly selected, age-stratified, sex-stratified and site-stratified population-based sample of 3048 adults aged ≥35 years from four resource-poor settings in Peru. We assessed baseline and annual pre-bronchodilator and post-bronchodilator lung function over 3 years. We used linear mixed-effects models to assess biological, socioeconomic and environmental risk factors associated with accelerated lung function decline. Results: Mean±SD enrolment age was 55.4±12.5 years, 49.2% were male and mean follow-up time was 2.36 (SD 0.61) years. Mean annual pre-bronchodilator FEV1 decline was 30.3 mL/year (95% CI 28.6 to 32.0) and pre-bronchodilator FVC decline was 32.2 mL/year (30.0 to 34.4). Using multivariable linear mixed-effects regression, we found that urban living, high-altitude dwelling and having hypertension accounted for 25.9% (95% CI 15.7% to 36.1%), 21.3% (11.1% to 31.5%) and 15.7% (3.7% to 26.9%) of the overall mean annual decline in pre-bronchodilator FEV1 /height 2, respectively. Corresponding estimates for pre-bronchodilator FVC/height 2 were 42.1% (95% CI% 29.8% to 54.4%), 36.0% (23.7% to 48.2%) and 15.8% (2.6% to 28.9%) of the overall mean annual decline, respectively. Conclusion: Urbanisation, living at high altitude and hypertension were associated with accelerated lung function decline in a population with low daily smoking prevalence.